3(w+7)=-3(7w-1)+9w

Simple and best practice solution for 3(w+7)=-3(7w-1)+9w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w+7)=-3(7w-1)+9w equation:


Simplifying
3(w + 7) = -3(7w + -1) + 9w

Reorder the terms:
3(7 + w) = -3(7w + -1) + 9w
(7 * 3 + w * 3) = -3(7w + -1) + 9w
(21 + 3w) = -3(7w + -1) + 9w

Reorder the terms:
21 + 3w = -3(-1 + 7w) + 9w
21 + 3w = (-1 * -3 + 7w * -3) + 9w
21 + 3w = (3 + -21w) + 9w

Combine like terms: -21w + 9w = -12w
21 + 3w = 3 + -12w

Solving
21 + 3w = 3 + -12w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '12w' to each side of the equation.
21 + 3w + 12w = 3 + -12w + 12w

Combine like terms: 3w + 12w = 15w
21 + 15w = 3 + -12w + 12w

Combine like terms: -12w + 12w = 0
21 + 15w = 3 + 0
21 + 15w = 3

Add '-21' to each side of the equation.
21 + -21 + 15w = 3 + -21

Combine like terms: 21 + -21 = 0
0 + 15w = 3 + -21
15w = 3 + -21

Combine like terms: 3 + -21 = -18
15w = -18

Divide each side by '15'.
w = -1.2

Simplifying
w = -1.2

See similar equations:

| 7c*6e= | | 8x+10y=48 | | 5a/4-2a/5=17/2 | | 2(x-3)-3=-4(-5x+3)-3x | | 3x+7-5(x-1)=5x+4 | | 8r+10y=48 | | 8x-9-6x+14=11x-9-10+13 | | -7.24=x/4+3 | | a*2/(4+6)=10 | | 15x^2+19m+6=0 | | -5x+15.8=3.3 | | 3-4(5-7)=z | | Z+6/8=Z-5/7 | | -3(3v-7)+7v=6+3(2v-1) | | -1.1+u/2=-13.9 | | 6=-19+t | | 7(x+4)=-3(x+2)+4 | | 5+2u=19 | | .3x+2=2.6 | | 25=-14+y | | -3+4(-2+7)= | | -24=w/4-4 | | (3)/(x^2-2x)-(2)/(x)=(8)/(x-2) | | 8+6v=6v-6+7v | | 3y-2+3(2y+1)=-3(y+3) | | 58=-x+171 | | y-(-9)=(-14/3)(x-(-9)) | | x/37+25=50 | | 7x+3=2x-17 | | 240=-w+30 | | (x+12)/(x-3)+1=(15)/(x-3) | | y-5=(-14/3)(x-(-6)) |

Equations solver categories